Economic evaluation of fecal microbiota transplantation for the treatment of recurrent Clostridium difficile infection in Australia. Issue 12 (29th November 2016) - Merlo, Gregory; Graves, Nicholas; Brain, David; Connelly, Luke B
Abstract: Background and Aim: Clostridium difficile is the most common cause of hospital‐acquired diarrhea in Australia. In 2013, a randomized controlled trial demonstrated the effectiveness of fecal microbiota transplantation (FMT) for the treatment of recurrent Clostridium difficile infection (CDI). The aim of this study is to evaluate the cost‐effectiveness of fecal microbiota transplantation—via either nasoduodenal or colorectal delivery—compared with vancomycin for the treatment of recurrent CDI in Australia. Methods: A Markov model was developed to compare the cost‐effectiveness of fecal microbiota transplantation compared with standard antibiotic therapy. A literature review of clinical evidence informed the structure of the model and the choice of parameter values. Clinical effectiveness was measured in terms of quality‐adjusted life years. Uncertainty in the model was explored using probabilistic sensitivity analysis. Results: Both nasoduodenal and colorectal FMT resulted in improved quality of life and reduced cost compared with vancomycin. The incremental effectiveness of either FMT delivery compared with vancomycin was 1.2 (95% CI: 0.1, 2.3) quality‐adjusted life years, or 1.4 (95% CI: 0.4, 2.4) life years saved. Treatment with vancomycin resulted in an increased cost of AU4094 (95% CI: AU26, AU8161) compared with nasoduodenal delivery of FMT and AU4045 (95% CI: −AU33, AU8124) compared with colorectal delivery. The mean difference in cost between colorectal and nasoduodenal FMT was not significant. Conclusions: If FMT, rather than vancomycin, became standard care for recurrent CDI in Australia, the estimated national healthcare savings would be over AU4000 per treated person, with a substantial increase in quality of life.